Decentralized cooperative tracking subject to motion constraints - Wang, Lin; Markdahl, Johan; Liu, Zhixin; Hu, Xiaoming (Automatica (Oxford), 2018)
This paper addresses the formation control problem, where three agents are tasked with moving an object cooperatively along a desired trajectory while also adjusting its posture to some desired attitudes, i.e. position and attitude tracking. Two decentralized control laws based on locally available information are proposed. The first control law maintains constant inter-agent distances over time, i.e. the formation of agents moves as a single rigid-body. The second control law relaxes this constraint by only maintaining similarity of the agent formation as a polygon in Euclidean space.